Pengaruh Pengetahuan Keuangan, Sikap Keuangan dan Kepribadian Terhadap Perilaku Manajemen Keuangan pada Pelaku UMKM di Kabupaten Tanah Laut - Desi Wardani; Bella Puspita Rininda; Widya Astuti Alam Sur; Noor Amelia (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2025)
This study aims to identify the impact of financial knowledge, attitude, and personality on financial management behaviour among SMEs, particularly in the culinary sector of Tanah Laut Regency. This research has novelty in integrating personality as a factor influencing the financial management behaviour of MSME actors, in addition to economic knowledge and financial attitudes that have been extensively studied previously. The population includes 2,055 SMEs in Tanah Laut Regency, with a sample size of 95 respondents. A quantitative approach is used in this research, with data collected through questionnaires. Data analysis involves descriptive statistics, data quality tests, classical assumption tests, and multiple linear regression to test the hypotheses. The research results show that financial knowledge does not affect financial management behaviour, nor does financial attitude have a significant impact. However, personality has been proven to influence how someone manages their finances. The results show that financial knowledge, financial attitudes, and personality contribute to variations in financial management behaviour but are primarily influenced by factors outside the scope of this study.